Menopause and chronic periodontitis in females attending Polyclinic, Kulliyyah of Dentistry, IIUM - Zulkeple, Md. Hafizul Taufiq; Zahuri, Muhammad Khairulanwar; Ridzuan, Taufik Firdaus; Hilal Abbood Al-Bayati, Lina; Faisal, Ghasak Ghazi; Mustafa Al-Ahmad, Basma Ezzat (2015)

(untitled)
Objectives: To investigate the severity of periodontal destruction among postmenopausal Malaysian women. Materials and methods: Case-control study was conducted in which 50 systematically healthy women who were diagnosed with chronic periodontitis participated in this study. Based on their menstruation status, they have been divided into two groups: control group included 25 women undergoing normal menstrual cycle, while the test group included 25 postmenopausal women. The clinical periodontal parameters were recorded, and the severity of the periodontal destruction was evaluated clinically according to the clinical attachment loss (CAL). Results: There were no significant differences between participants of the control and test groups in the percentages of sites with the presence of plaque and bleeding on probing (p>0.05). On the other hand, significant differences were found between both groups in their percentages of sites with (CAL) of 4-6 mm (p=0.013) and number of missing teeth (p=0.028). Conclusions: The findings of the present study suggest that postmenopausal women have more severe periodontal destruction compared to premenopausal. Keywords: postmenopausal women, chronic periodontitis, clinical attachment loss.